2022
DOI: 10.1007/s12011-022-03158-x
|View full text |Cite
|
Sign up to set email alerts
|

Essential Metals and Trace Elements in Cereals and Their Derivatives Commercialized and Consumed in Cape Verde

Abstract: Cereals and their derivatives are basic foods in the human diet and a source of minerals, but the content of elements may vary depending on the type of cereal or its processing. The levels of Na, K, Ca, Mg, Fe, Cu, Zn, Mo, Co, and Mn have been determined in 126 samples of cereals and cereal derivatives (rice, corn gofio, corn flour, wheat flour, corn, and wheat) commercialized and consumed in Cape Verde using an inductively coupled plasma-optical emission spectrometer (ICP-OES) after a wet microwave digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The correlation between the analysed variables in the data was illustrated in its raw form. For greater reliability in mineral composition correlations and quality assessment issues, the revealed findings were compared to previous studies (Ikem et al ., 2023; Rubio‐Armendáriz et al ., 2023), in which the researchers reported that the associations between the nutritional composition of cereal grains vary by geographical source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between the analysed variables in the data was illustrated in its raw form. For greater reliability in mineral composition correlations and quality assessment issues, the revealed findings were compared to previous studies (Ikem et al ., 2023; Rubio‐Armendáriz et al ., 2023), in which the researchers reported that the associations between the nutritional composition of cereal grains vary by geographical source.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, processing cereal grains for human consumption is crucial due to their geographical influence on their nutritional properties (Ikem et al ., 2023; Rubio‐Armendáriz et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Crude protein, acid detergent fiber, neutral detergent fiber, and crude fat in the Leymus chinensis hay and alfalfa hay samples were determined using an Automatic Kjeldahl Protein/Nitrogen Analyzer (K1160, Hanon Advanced Technology Group, China), Automatic Fiber Analyser (F2000, Hanon Advanced Technology Group, China) and Automatic Soxhlet Extractor (SOX606, Hanon Advanced Technology Group, China) respectively with reference to Shi et al ( 24 ). The content of mineral elements was determined with using microwave (REVO, LabTech, China) and inductively coupled plasma-optical emission spectrometer (PQ 9000, analytikjena, German) ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, they were transferred to an oven-muffle (Nabertherm, Lilienthal, Germany), whose temperature increased by 50 °C every hour for 24 h. Once the temperature of 425 ± 15 °C was reached, it was maintained for 24 h, thus achieving incineration of the samples. The white ashes obtained were dissolved to a volume of 25 mL in 1.5% HNO 3 (Sigma Aldrich, Taufkirchen, Germany) [ 63 , 64 , 65 ].…”
Section: Methodsmentioning
confidence: 99%